2018
DOI: 10.1093/ofid/ofy063
|View full text |Cite|
|
Sign up to set email alerts
|

Challenges Across the HIV Care Continuum for Patients With HIV/TB Co-infection in Atlanta, GA

Abstract: BackgroundAntiretroviral therapy (ART) for persons with HIV infection prevents tuberculosis (TB) disease. Additionally, sequential ART after initiation of TB treatment improves outcomes. We examined ART use, retention in care, and viral suppression (VS) before, during, and 3 years following TB treatment for an inner-city cohort in the United States.MethodsRetrospective cohort study among persons treated for culture-confirmed TB between 2008 and 2015 at an inner-city hospital.ResultsAmong 274 persons with cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Among 91 HIV-positive patients who survived >14 days after TB diagnosis, 74 (81%) received antiretroviral therapy (ART) during TB treatment and 47 (52%) had viral suppression at end of TB treatment. 16 There were more treatment interruptions due to AE among HIV-positive patients (34% vs. 15%), including of rifamycins (23% vs. 8%), isoniazid (24% vs. 10%), and pyrazinamide (19% vs. 8%) (all with p £ .01) compared to HIV-negative patients (Table 2). Similarly, hepatotoxicity was more common among HIV-positive patients compared to HIV-negative patients (13% vs. 3%, p £ .01).…”
Section: Comparison Of Characteristics and Complexities According To Hiv Infectionmentioning
confidence: 98%
“…Among 91 HIV-positive patients who survived >14 days after TB diagnosis, 74 (81%) received antiretroviral therapy (ART) during TB treatment and 47 (52%) had viral suppression at end of TB treatment. 16 There were more treatment interruptions due to AE among HIV-positive patients (34% vs. 15%), including of rifamycins (23% vs. 8%), isoniazid (24% vs. 10%), and pyrazinamide (19% vs. 8%) (all with p £ .01) compared to HIV-negative patients (Table 2). Similarly, hepatotoxicity was more common among HIV-positive patients compared to HIV-negative patients (13% vs. 3%, p £ .01).…”
Section: Comparison Of Characteristics and Complexities According To Hiv Infectionmentioning
confidence: 98%
“…Variable measurements: adherence was measured by assessing the number of missed clinic appointments. It was categorised into two groups “good adherence”, those who attained greater than 90% of appointment visits and “poor adherence”, those who achieved less than 90% of scheduled clinic appointments [ 19 , 20 ]. The exposure variables were: demographic (sex, age, marital status); socio-economic (source of income, educational level); laboratory (AAFB test, CD4 count); clinical (other opportunistic infections and duration on HIV treatment).…”
Section: Methodsmentioning
confidence: 99%
“…This fundamental paradigm shift in medication adherence would have a resultant effect in reduction of HIV transmission and would prolong and improve the quality of life of those infected [ 18 , 19 ]. Despite the advances in treatment availability and accessibility, TB/HIV co-infection has remained a compounded public health challenge [ 20 ] requiring innovative approach specifically in South Africa, a high burden country. Therefore, assessing the determinants of adherence to clinic appointments among TB/HIV infected patients is critical to help identify effective health system interventions that could be used to support individuals taking both TB medication and ART for improved treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…From the results of drug susceptibility experiments, 113 cases of multidrugresistant strains were finally detected, of which 82 cases had rpoB gene mutations, and the gene mutation rate was 55.75%. The mutation ranged from codon 511 to codon 569, and 73 cases (89.02%) had mutations in the rifampicin resistance determining region (RRDR), which suggested that this region was the main mutation location that led to rifampicin resistance (27). In addition, the mutation frequency of codon 528 was the highest (54.08%), and the corresponding amino acid changes were Ser→Leu and Ser→Phe, which indicated that the mutation at this codon site was polymorphic.…”
Section: Gene Mutation Characteristics Of Multidrugresistant Mtbmentioning
confidence: 99%